Analyzing the Relationship between Earnings Quality and Financial Ratios Derived from Cash Flow Statement (An Applied Study on Saudi Telecommunication Companies) - Baaqeel, Fatmah Mohammad; Abdulrahman, Najla Ibrahim (Journal of Economic, Administrative and Legal Sciences, 2020)
The aim of this research is to analyze the relationship between earnings quality and financial ratios derived from cash flows statement of telecom sector companies in the Saudi Stock Market. The analyzing period was from 2009 to 2018, assuming there is a significant relationship between operating cash ratio, operational activity index, adequacy cash flow and return on assets from operating cash flow on earnings quality. Calculating ratios and earnings quality through published financial statements and reports to find the relationship between the variables using multiple regression model. Findings indicate no relationship between earnings quality and both operating cash ratio and the operational activity index, and there is a direct relationship between earnings quality and adequacy cash flow, and an inverse relationship between earnings quality and return on assets from the operating cash flow. The researcher recommends decision-makers to pay more attention to the ratios related to the earnings quality, and do more research related to the subject.